2010
DOI: 10.1007/s10534-010-9326-0
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the divalent metal transporter 1 increases bleomycin-induced lung injury

Abstract: Exposure to bleomycin can result in an inflammatory lung injury. The biological effect of this anti-neoplastic agent is dependent on its coordination of iron with subsequent oxidant generation. In lung cells, divalent metal transporter 1 (DMT1) can participate in metal transport resulting in control of an oxidative stress and tissue damage. We tested the postulate that metal import by DMT1 would participate in preventing lung injury after exposure to bleomycin. Microcytic anemia (mk/mk) mice defective in DMT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Interestingly, bleomycin directly complexes redox-active iron resulting in DNA degradation and iron deficiency or chelation is associated with a reduction in the severity of bleomycin-induced pulmonary fibrosis. Similarly, an iron-depleted diet diminishes fibrotic injury after dust instillation, whereas loss of DMT1 increases bleomycin-induced lung injury [150][151][152][153][154]. Another recent study showed that a FPN1 mutation resulted in iron accumulation in AMs and lung epithelial cells with subsequent development of restrictive lung disease [155].…”
Section: Interstitial Lung Diseasesmentioning
confidence: 99%
“…Interestingly, bleomycin directly complexes redox-active iron resulting in DNA degradation and iron deficiency or chelation is associated with a reduction in the severity of bleomycin-induced pulmonary fibrosis. Similarly, an iron-depleted diet diminishes fibrotic injury after dust instillation, whereas loss of DMT1 increases bleomycin-induced lung injury [150][151][152][153][154]. Another recent study showed that a FPN1 mutation resulted in iron accumulation in AMs and lung epithelial cells with subsequent development of restrictive lung disease [155].…”
Section: Interstitial Lung Diseasesmentioning
confidence: 99%
“…The Belgrade rat, an animal model of functional DMT1 deficiency, develops more severe lung injury in response to lipopolysaccharide (LPS) and oil fly ash [23,24]. Similarly, mk / mk mice, also defective in DMT1, have increased bleomycin-induced lung injury compared to wild-type controls [25]. The mechanism of DMT1 attenuating the lung’s response to inflammatory stimuli is unclear, but these descriptive studies demonstrate a link between DMT1 and the lung’s inflammatory response.…”
Section: Iron Regulationmentioning
confidence: 99%